2019
DOI: 10.3390/catal9030233
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanoparticles’ Morphological Effects on the N2O Decomposition Performance of Co3O4/CeO2 Mixed Oxides

Abstract: Ceria-based oxides have been widely explored recently in the direct decomposition of N2O (deN2O) due to their unique redox/surface properties and lower cost as compared to noble metal-based catalysts. Cobalt oxide dispersed on ceria is among the most active mixed oxides with its efficiency strongly affected by counterpart features, such as particle size and morphology. In this work, the morphological effect of ceria nanostructures (nanorods (ΝR), nanocubes (NC), nanopolyhedra (NP)) on the solid-state propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 74 publications
3
17
0
Order By: Relevance
“…Based on our recent XPS study using appropriate standards [14,26,34] and work [35], we assigned the component with lower BE (780 eV) to tetrahedral Co 2+ and the component with higher BE (782 and 783.5 eV) to octahedral Co 3+ . However, in the literature can also be found opposite assignment [36][37][38][39]. These findings could be explained by the position of maxima for Co(OH) 2 , which is located at the position of second fitting peak of Co 3 O 4 [32].…”
Section: Xpsmentioning
confidence: 87%
“…Based on our recent XPS study using appropriate standards [14,26,34] and work [35], we assigned the component with lower BE (780 eV) to tetrahedral Co 2+ and the component with higher BE (782 and 783.5 eV) to octahedral Co 3+ . However, in the literature can also be found opposite assignment [36][37][38][39]. These findings could be explained by the position of maxima for Co(OH) 2 , which is located at the position of second fitting peak of Co 3 O 4 [32].…”
Section: Xpsmentioning
confidence: 87%
“…The Fe2O3/CeO2-NX mixed catalysts were prepared by the wet impregnation method, employing an aqueous solution of Fe(NO3)3•9H2O, in order to obtain an atomic ratio Fe/(Fe+Ce) of 0.2, which corresponds to a Fe loading of 7.5 wt.%. This particular ratio was dictated from our previous studies over a series of MOx/CeO2 catalysts where the M/(M + Ce) atomic content is always kept constant to 0.2 [18,78]. Moreover, relevant literature studies over FeOx/CeO2 catalysts revealed that optimum redox/surface properties can be obtained at similar metal contents, e.g.…”
Section: Materials Synthesismentioning
confidence: 99%
“…On the other hand, metal oxides (MOs) prepared from earth-abundant, and inexpensive transition metals have attracted considerable attention as alternatives to rare and expensive NMs, due to their particular features, such as enhanced redox properties, thermal stability and catalytic performance in conjunction to their lower cost [2,3,5,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The latter is clearly manifested in Figure 1, which schematically depicts the cost of noble metals in comparison with copper (a typical transition metal massively involved in MOs) for the past five-year period.…”
Section: Introductionmentioning
confidence: 99%